DETERMINING THE EFFICIENCY OF USING AND CLEANING THE ROTOR-FILTER DEVICE IN NEUTRALIZING HYDROGEN-FLUORITE (2HF) GAS (American Journal of Interdisciplinary Research and Development, 2024)
The article presents experiments on trapping toxic gases in mixing reactors during superphosphate mineral fertilizer production using a proposed rotor filter apparatus. Experiments were conducted on various absorbents based on gas speed entering the rotor-filter apparatus. Results were presented in tables and graphs. Results of the conducted experiment, a histogram of the dependence of liquid consumption and gas velocity on cleaning efficiency was constructed using EXM. In addition, the selection of the optimal value of the hydraulic resistance in the fan and smoke pipe, which absorbs toxic gases and dusty air, was analyzed with the help of graphs and tables, and the obtained results were cited.